Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To solve the equation [tex]\( 3^{x^2 + 6x} = 9^{-4} \)[/tex], let's follow these detailed steps:
1. Rewrite the Right-Hand Side:
Notice that 9 can be written as [tex]\( 3^2 \)[/tex]. Thus, [tex]\( 9^{-4} \)[/tex] can be rewritten using base 3:
[tex]\[ 9^{-4} = (3^2)^{-4} \][/tex]
Applying the power of a power rule [tex]\((a^m)^n = a^{mn}\)[/tex], we get:
[tex]\[ 9^{-4} = 3^{2 \cdot (-4)} = 3^{-8} \][/tex]
2. Set Exponents Equal:
Now that both sides of the equation have the same base (3), we can equate the exponents:
[tex]\[ 3^{x^2 + 6x} = 3^{-8} \quad \Longrightarrow \quad x^2 + 6x = -8 \][/tex]
3. Form a Quadratic Equation:
The above equation is a standard quadratic equation. Rewrite it in the standard form:
[tex]\[ x^2 + 6x + 8 = 0 \][/tex]
4. Solve the Quadratic Equation:
To solve [tex]\( x^2 + 6x + 8 = 0 \)[/tex], we use the quadratic formula [tex]\( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 1 \)[/tex], [tex]\( b = 6 \)[/tex], and [tex]\( c = 8 \)[/tex].
First, compute the discriminant:
[tex]\[ b^2 - 4ac = 6^2 - 4 \cdot 1 \cdot 8 = 36 - 32 = 4 \][/tex]
Next, calculate the values of [tex]\( x \)[/tex]:
[tex]\[ x = \frac{-6 \pm \sqrt{4}}{2 \cdot 1} = \frac{-6 \pm 2}{2} \][/tex]
This gives us two solutions:
[tex]\[ x = \frac{-6 + 2}{2} = \frac{-4}{2} = -2 \][/tex]
[tex]\[ x = \frac{-6 - 2}{2} = \frac{-8}{2} = -4 \][/tex]
5. Conclusion:
The solutions to the equation [tex]\( 3^{x^2 + 6x} = 9^{-4} \)[/tex] are:
[tex]\[ x = -2, -4 \][/tex]
1. Rewrite the Right-Hand Side:
Notice that 9 can be written as [tex]\( 3^2 \)[/tex]. Thus, [tex]\( 9^{-4} \)[/tex] can be rewritten using base 3:
[tex]\[ 9^{-4} = (3^2)^{-4} \][/tex]
Applying the power of a power rule [tex]\((a^m)^n = a^{mn}\)[/tex], we get:
[tex]\[ 9^{-4} = 3^{2 \cdot (-4)} = 3^{-8} \][/tex]
2. Set Exponents Equal:
Now that both sides of the equation have the same base (3), we can equate the exponents:
[tex]\[ 3^{x^2 + 6x} = 3^{-8} \quad \Longrightarrow \quad x^2 + 6x = -8 \][/tex]
3. Form a Quadratic Equation:
The above equation is a standard quadratic equation. Rewrite it in the standard form:
[tex]\[ x^2 + 6x + 8 = 0 \][/tex]
4. Solve the Quadratic Equation:
To solve [tex]\( x^2 + 6x + 8 = 0 \)[/tex], we use the quadratic formula [tex]\( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 1 \)[/tex], [tex]\( b = 6 \)[/tex], and [tex]\( c = 8 \)[/tex].
First, compute the discriminant:
[tex]\[ b^2 - 4ac = 6^2 - 4 \cdot 1 \cdot 8 = 36 - 32 = 4 \][/tex]
Next, calculate the values of [tex]\( x \)[/tex]:
[tex]\[ x = \frac{-6 \pm \sqrt{4}}{2 \cdot 1} = \frac{-6 \pm 2}{2} \][/tex]
This gives us two solutions:
[tex]\[ x = \frac{-6 + 2}{2} = \frac{-4}{2} = -2 \][/tex]
[tex]\[ x = \frac{-6 - 2}{2} = \frac{-8}{2} = -4 \][/tex]
5. Conclusion:
The solutions to the equation [tex]\( 3^{x^2 + 6x} = 9^{-4} \)[/tex] are:
[tex]\[ x = -2, -4 \][/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.